Kilmacreehy church, south chancel wall, tomb niche, jamb - O'Donovan, Danielle (My University, 2008)
Jamb of reconstructed tomb niche. Moulding comprises corner roll, flanked at either side by fillet and hollow. Looks twelfth- or thirteenth-century but may be revival of these forms from the fifteenth century.
Tomb niche
Keywords: Architecture, Gothic -- Ireland; Clare (Ireland)--Antiquities.; Funerary monuments; Late Medieval; roll moldings; moldings, hollow